Toward a Contingency Model of Strategic Risk Taking - Baird, Inga S.; Thomas, Howard (Academy of Management Review, 1985)
A model of strategic risk taking incorporating environmental, industrial, organizational, decision maker, and problem variables is presented. The model is intended to be both a preliminary conceptualization of strategic risk taking and a stimulant for future research on risk taking in strategic management decisions. Relevant research from a number of disciplines is summarized, and the potential impacts of particular variables on the propensity to take strategic risks are examined.